2020
DOI: 10.3389/fpsyg.2020.00710
|View full text |Cite
|
Sign up to set email alerts
|

Homophily in Personality Enhances Group Success Among Real-Life Friends

Abstract: Personality affects dyadic relations and teamwork, yet its role among groups of friends has been little explored. We examine for the first time whether similarity in personality enhances the effectiveness of real-life friendship groups. Using data from a longitudinal study of a European fraternity (10 male and 15 female groups), we investigate how individual Big Five personality traits were associated with group formation and whether personality homophily related to how successful the groups were over 1 year (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 58 publications
0
13
1
Order By: Relevance
“…Previous study only shows that matching level of Extraversion leads to positive emotional expressions [17] and that may not be a essential factor of friendship building. Unlike the past study [16], the Synchrony of both Conservation vs. Openness to Change and Self-transcendence vs. Self-enhancement revealed positive relationship with the synchrony of the friendship quality.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Previous study only shows that matching level of Extraversion leads to positive emotional expressions [17] and that may not be a essential factor of friendship building. Unlike the past study [16], the Synchrony of both Conservation vs. Openness to Change and Self-transcendence vs. Self-enhancement revealed positive relationship with the synchrony of the friendship quality.…”
Section: Discussioncontrasting
confidence: 85%
“…Given that the personality traits were not specified in that study, it is intriguing whether a certain aspect in one's personality could possibly predict the friendship quality. A more recent study also showed similar results that personality similarity was positively correlated with group success, even after controlling for individual's own personality [16], demonstrating the crucial role of personality similarity in the interaction among group members.…”
Section: Introductionmentioning
confidence: 59%
“…One complicating aspect of real social networks not usually considered in these models is the fact that social subnetworks are characterized by a high level of homophily, especially in the inner layers. In other words, people's friends tend to resemble them on an array of social and cultural dimensions [118,119,123]. Analysing a large (20 million users) cellphone dataset, Miritello et al [85] differentiated, on the basis of calling patterns, two distinct phenotypes: 'social keepers' who focused their calls on a small, stable cohort of contacts (introverts?)…”
Section: Propagation In Structured Networkmentioning
confidence: 99%
“…Homophily in friendships has also been documented in respect of a number of endogenous traits, including gender [17,24,66,121], ethnicity [122] and personality [85,123]. Gender has a particularly strong effect: approximately 70% of men's social networks consist of men, and approximately 70% of women's networks consist of women, with most of the opposite sex alters in both cases being extended family members.…”
Section: Time Trust and The Bonds That Bindmentioning
confidence: 99%
“…Uncertainty reduction theory suggests that shared values make interaction partners more predictable, easing communication and supporting friendship formation (Berger and Calabrese 1975). Several empirical studies show that homophily regarding personality traits plays a role in forming new friendships in larger social environments (Bahns et al 2017;Selden and Goodie 2018;Laakasuo et al 2020). University students tend to select friends with similar levels of extraversion, agreeableness, and openness and the perceived similarity in personality traits predicts students' higher friendship intensity (Selfhout et al 2009).…”
Section: The Effect Of Student-environment-fit On Social Integrationmentioning
confidence: 99%